Eksistensi Penggunaan Bahasa Indonesia yang Baku di Kalangan Remaja - Syahputra, Edi; Gustiana, Dinda; Lestari, Tiara Dwi; Fadhilah, Qorri; Hidayat, Yulia (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
When it comes to knowledge and technology, globalization has a huge impact on the daily lives of a wide range of people including the young. There are a lot of different ways to express yourself, from how you live your life to the language you use. There may be a large number of people who feel cheated if they use an Indonesian language that is accurate and up-to-date. As a result, the language is a major source of pride for the nation. As a generation of people, we must be capable of communicating with other countries in Indonesian as a form of pen-to-paper diplomacy. Using a language that isn’t your native tongue is a common occurrence in the surrounding environment, and ironically, this has been viewed as a sign of progress. One of the main reasons for the difficulty in using the Indonesian language is the influence of other languages or modernization. This is a common occurrence among Roman Catholics throughout the country. Indonesian Bahasa baku has been caused by the development of the Gaul language. They’ll forget to speak in Indonesian while they’re discussing official matters, even though they’re used to speaking in Gaul. As a result, all parties who are interested in using the Indonesian language in a proper and accurate manner will need to pay attention to this situation. Among other things, we may tell the Indonesian people, especially the descendants of the Bangsa Penerus generation,that Indonesian is a national language and must be spoken.